An Interaction between Firm Strategy, Capital Structure and Firm’s Performance - Ramakrishnan, Suresh; ., Saqib Muneer; ., Melati Ahmad Anuar (Journal of Economics and Behavioral Studies, 2015)
The study tries to determine the association among corporate strategy, social structure and firm performance. In this regard, the monetary reports of 78 companies listed in Karachi Stock Exchange since 2007 to 2014 were scrutinized. In this research, firm strategy (sales growth, liquidity) and capital structure (debt ratio) were used as sovereign variables, and firm performance (return on equity, return on assets, free cash flow for the firm, free cash flow per share) were functional and are used as dependent variables, so to study the affiliation between corporate strategy, capital structure and firm performance within a 8-years period from 2007 to 2014. Secondary data has been used to test the hypotheses; single variable linear regression method was used and their significance was evaluated using Statistics T (t-test) and F (Fisher). The study results indicate that there is a significant positive relationship between sales growth variables and two types (among four types) of performance criteria in the study, namely return on equity and return on assets. And there is a positive significant relationship between firm liquidity and three criteria of firm’s performance in the study namely return on equity, free cash flow per share and return on assets. Also, debt ratio has a positive significant relationship with free cash flow for firm and a negative significant relationship with return on assets.